The Effect Of Video-Based Health Promotion On Knowledge And Readiness To Face Menarche Among Female Students At MI Nurul Ihsan Buminabung Timur, Central Lampung Regency - Lilis Sri Utami; Sri Nowo Retno; Linda Puspita; Komalasari, Komalasari (Sean Institute, 2024)
According to the World Health Organization (WHO) in 2021, around 14% of the 12 billion adolescents in the world aged 10-19 experience anxiety before puberty. The most important event that occurs during puberty for adolescent girls is menarche. Problems facing menarche include anxiety caused by negative perceptions of menstruation that lead to feelings of fear, anxiety, and worry. The purpose of this study was to determine the effect of video-based health promotion on knowledge and readiness to face menarche among female students at Madrasah Ibtidaiyah (MI) Nurul Ihsan Bumi Nabung Timur, Central Lampung Regency in 2024. This research is a quantitative analytic study with a pre-experimental approach using a one-group pretest-posttest design. The population in this study was all female students in grades 5-6 who had not experienced menarche, with a population and sample size of 17 female students using a total sampling technique. Data collection was done using a questionnaire. Univariate data analysis used mean calculations, while bivariate analysis used chi-square. The results showed that the average pretest knowledge was 4.59, and the pretest readiness to face menarche was 18.47. The average posttest knowledge was 9.94, and the posttest readiness was 25.24. There was an effect of video-based health promotion on knowledge about menarche (p-value: 0.000). There was an effect of video-based health promotion on readiness to face menarche (p-value: 0.000). It is recommended that the school can develop a sustainable health promotion program in collaboration with related parties such as the community health center (puskesmas) and other health workers.